Integrating courtyard microclimate in building performance to mitigate extreme urban heat impacts. (March 2022) - Lizana, Jesus; López-Cabeza, Victoria Patricia; Renaldi, Renaldi; Diz-Mellado, Eduardo; Rivera-Gómez, Carlos; Galán-Marín, Carmen
Highlights: Specific urban microclimates are not considered by building energy simulation tools. Numerical modelling with multi-nodal outdoor conditions is developed. The aim is to quantify the benefits of specific microclimates in building performance. A reference case with a courtyard microclimate was measured, simulated and validated. Courtyard microclimate mitigates the impact of extreme urban heat in buildings. Abstract: Extreme heat events are expected to occur more often as a consequence of climate change. This paper quantifies the impact of urban climate on building performance and evaluates the benefits of specific microclimates, such as inner courtyards, to mitigate extreme heat impacts. A reference case study associated with two outdoor weather conditions, an inner courtyard and a local urban climate, was measured, simulated and validated in TRNSYS. The validated model was then compared to three building models with a single outdoor weather condition associated with the urban climate, weather data from a rural station and a typical year weather file. The models were evaluated in free-running conditions and with air-conditioning systems. The results show how urban climate can increase indoor discomfort hours by 32% in free-running conditions and demonstrate that courtyard microclimate can almost completely mitigate the impact of urban overheating in buildings, eliminating severe indoor discomfort hours by more than 88%. Moreover, the increase in cooling energy demand due to urban climate was reduced by more than 15% in the case of having air-conditioning systems. The findings manifest the importance of accurate weather data for building simulation and demonstrate how multi-nodal outdoor conditions can enable additional strategies to mitigate climate risks, highlighting urban microclimates as a promising strategy to tackle extreme heat events in buildings and cities.